Scanning electron microscopic evaluation of efficacy of 17% Ethylenediaminetetraacetic acid and chitosan for smear layer removal with ultrasonics: An In vitro study - Aradhana Babu Kamble; Sathish Abraham; Deepak Dadarao Kakde; C Shashidhar; Disha Lalit Mehta (Wolters Kluwer Medknow Publications, 2017)
Introduction: The main aim of root canal treatment is cleaning, shaping and then obturating three dimensionally to prevent reinfection. This includes chemicomechanical cleansing by instrumentation and the use of irrigating solutions. Therefore, the purpose of this study was to compare the smear layer removal from root canal dentine subjected to two root canal irrigants, 17% EDTA and 0.2% Chitosan, a new irrigant using Scanning Electron Microscope. Methodology: 40 single rooted premolars were decoronated followed by instrumentation with I Race files and intermediate irrigation with 3% sodium hypochlorite and activation with ultrasonics. Then the samples were longitudinally sectioned and place in the respective test solutions and their controls for 5 minutes. Scanning Electron Microscopic evaluation was further carried out. Results: The results of the present study indicates that the Chitosan which was proved effective in removing smear layer. Conclusion: A moderate concentration of 0.2% chitosan removes the smear layer with greater efficiency.